2012
DOI: 10.1093/cercor/bhs081
|View full text |Cite
|
Sign up to set email alerts
|

Multiplicative Mechanism of Lateral Interactions Revealed by Controlling Interhemispheric Input

Abstract: Long-range horizontal connections are thought to modulate the responsiveness of neurons by supplying contextual information. A special type of long-range connections are interhemispheric projections, linking the 2 cerebral hemispheres. To investigate the action of those projections in a causal approach, we recorded in cat primary visual cortex while deactivating corresponding regions on the contralateral hemisphere. Interestingly, the action of callosal projections turned out to depend on the local and global … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(47 citation statements)
references
References 73 publications
5
42
0
Order By: Relevance
“…2B, gray dots) and decrease (black dots) across all contrasts. In agreement with our previous studies (Schmidt et al, 2010;Wunderle et al, 2013), only a few neurons increased their activity upon thermal deactivation (n ϭ 11, 7.7% of total multiunits).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…2B, gray dots) and decrease (black dots) across all contrasts. In agreement with our previous studies (Schmidt et al, 2010;Wunderle et al, 2013), only a few neurons increased their activity upon thermal deactivation (n ϭ 11, 7.7% of total multiunits).…”
Section: Resultssupporting
confidence: 93%
“…This is in line with previous reports (Payne et al, 1991;Sun et al, 1994;Schmidt et al, 2010;Peiker et al, 2013;Wunderle et al, 2013) and the predominant excitatory nature of the interhemispheric connections (for review, see Conti and Manzoni, 1994). The rate decreases we observed are surprisingly strong, given the small fraction of callosal synapses on a typical dendritic tree (Porter and White, 1986).…”
Section: Input and Output Gain Modulation Through The Interhemispherisupporting
confidence: 92%
See 1 more Smart Citation
“…Changes include both increases and decreases of spontaneous and evoked discharges of single units Payne and Siwek, 1991;Sun et al, 1994), pointing to complex excitatory and inhibitory effects exerted by interhemispheric connections. Schmidt and collaborators (Schmidt et al, 2010;Wunderle et al, 2013) have also reported a mixture of excitation and inhibition in cats and ferrets, but the facilitating effects of callosal input appeared to predominate in the recordings. Interestingly, the excitatory/inhibitory effects of interhemispheric connections were found to depend on the level of feed-forward drive provided by visual stimulation (Wunderle et al, 2013).…”
Section: Physiology Of Visual Interhemispheric Connections: Lessons Fmentioning
confidence: 95%
“…Schmidt and collaborators (Schmidt et al, 2010;Wunderle et al, 2013) have also reported a mixture of excitation and inhibition in cats and ferrets, but the facilitating effects of callosal input appeared to predominate in the recordings. Interestingly, the excitatory/inhibitory effects of interhemispheric connections were found to depend on the level of feed-forward drive provided by visual stimulation (Wunderle et al, 2013). In particular, stimulation with high-contrast, full-field gratings revealed both excitatory and inhibitory transcallosal Brought to you by | Western University Authenticated Download Date | 6/9/15 10:16 PM actions, while almost exclusively facilitating effects were detected with a less salient and unstructured stimulus (random dot textures).…”
Section: Physiology Of Visual Interhemispheric Connections: Lessons Fmentioning
confidence: 95%